Integrasi Filsafat dan Pendidikan: Metodologi Keilmuan Muhammad Iqbal dalam Bingkai Pengembangan Pendidikan Agama Islam - Zeni Murtafiati Mizani; Usman; Sibawaihi (https://ejournal.insuriponorogo.ac.id/, 2025)
This study raises Muhammad Iqbal's thoughts on the formulation of scientific methodology that integrates philosophy and education, especially in the development of comprehensive and transformative Islamic Religious Education (PAI). The background of this study departs from the reality of being divided into two between Western education and traditional Islamic education which tends to be speculative and less responsive to the development of science and technology. Muhammad Iqbal offers a new framework of thought by emphasizing the importance of synthesis between empirical experience and spiritual intuition as the basis of Islamic epistemology. This study uses a qualitative approach with a library research method. Data were obtained through a literature review of Iqbal's primary and secondary works, and were analyzed using content analysis, historical analysis, and narrative-philosophical analysis methods. The research findings show that Muhammad Iqbal's educational thoughts include the duality of physics and metaphysics, and emphasize the importance of developing individuality, physical-spiritual integration, and the role of the intellect and the whispers of the heart in the educational process. His scientific construction makes a significant contribution to the formulation of educational goals, student character, curriculum, and learning methods in PAI. Thus, Iqbal's thoughts are relevant as a basis for reformulating an Islamic education model that is contextual, rational, and remains rooted in Islamic spiritual values.